PENGARUH KONSEP DIRI DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR ILMU PENGETAHUAN SOSIAL (SURVEI PADA MTs NEGERI KAB. INDRAMAYU) - Toni, Ahmad Alim (LPPM STKIP Pangeran Dharma Kusuma Segeran Juntinyuat Indramayu, 2024)
The purpose of this study is to determine 1). The influence of self-concept and learning motivation on social studies learning achievement MTs Negeri Indramayu 2). The influence of self-concept on student social studies achievement of MTs Negeri Indramayu District, 3) The influence of learning motivation on student learning achievement in social studies samples used 70 students with multiple linear regression analysis model. Research results show that: 1) There is a significant of self-concept and learning motivation on student IPS learning achievement of MTs Negeri Indramayu District. This is evidenced by the value of Sig = 0.000 <0.05 and Fcount = 62,832,. 2). There is a significant influence of learning motivation on student IPS learning achievement of MTs Negeri Indramayu District. This is evidenced by the value of Sig = 0.000 <0.05 and tcount = 7,435, 3). There is a significant effect of learning motivation on students’ social studies achievement of MTs Negeri Indramayu District. This is evidenced by the value of Sig = 0.000<0.05 and tcount = 4,417